PENGARUH IDENTITAS MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA DI HASIFMON - Aji Saputra; Bayu Efendy; Frendi Tobing; Muhammad Prasetya; Muhammad Syadied; Ni Nyoman Sawitri (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
The purpose of this study is to find out how brand identity, product quality, and promotion affect consumer purchasing decisions in Hasifmon. The number of samples taken from all members of the population was thirty respondents. Primary data, questionnaires, were used to conduct this study, and a partial linear regression method was used. The results of the study show that brand identity, product quality, and promotion greatly influence Hasifmon's purchase decision.